Wettability property of CNT-graphene like film deposited by microwave plasma enhanced vapor deposition technique. Issue 6 (3rd June 2019) - Bisht, Atul; Chockalingam, S.; Panwar, O. S.
Abstract: Wettability property of carbon nano-tubes (CNT)-graphene like films have been investigated. In this work, we have studied the wettability of CNT-graphene like film deposited on Ni substrate by Microwave Plasma Enhanced vapor deposition Technique (MWPECVD). Compared to the water contact angles of 77.8° for bare Ni substrate, the water contact angle of the CNT-graphene like hybrid films is found to be 128.4°. The nanostructures have been deposited at fixed pressure of 20 Torr with different temperature of 500, 600 and 700 °C. The results indicate that wettability properties of nano-structure can be tailored, significantly. The solid surface energy (SE) of composite films was estimated using contact angle measurements. The wettability of CNT-graphene has been studied first time in film form.